PENGARUH PROFESIONALISME DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALLITAS DALAM PEMERIKSAAN LAPORAN KEUANGAN PADA KANTOR AKUNTAN PUBLIK DI BALI - Ni Putu Apriliana Devi; Anak Agung Ketut Agus Suardika (Hita Akuntansi dan Keuangan, 2020)
This study aims to determine thei effect ofi professionalism and professional ethics on thei considerationi ofi thei level ofi materiality in thei examinationi ofi financial statements at public accountingi firms in Balii. thei total populationi in this study was 99 auditoris spread throughout thei Public Accountingi Firm (KAP) in Balii. Based on thei considerations, 82 people were sampled in this study. thei datai analysis technique used is multiple linear regression statistical analysis. Based on thei results ofi datai analysis, thei results show that professionalism has a positive effect on thei considerationi ofi materiality level in auditingi financial statements in KAP in Balii and professional ethics has a positive effect on thei considerationi ofi materiality level in auditingi financial statements on KAP in Balii.